Salivary Sex Steroid Levels in Infants and the Relation with Infantile Colic - Fulya Mete Kalaycı; Özlem Gürsoy Doruk; İbrahim Mert Erbaş; Osman Tolga İnce; Makbule Neslişah Tan; Adem Aydın; Ayhan Abacı; Ece Böber; Korcan Demir (Galenos Yayincilik, 2024)
INTRODUCTION: The hypothalamic-pituitary-gonadal axis is active during minipuberty, the timing of which coincides with infantile colic. To the best of our knowledge, the relationship between these entities has not been previously investigated. METHODS: Saliva samples were collected from 15- to 60-day-old term infants (n=139) between 9 am and 5 pm. Group 1 included infants with infantile colic (n=68, 54.4% female) while the remaining healthy infants constituted Group 2 (n=71, 47.9% female). Salivary levels of estradiol (Esal) in females and testosterone (Tsal) in males were measured by ELISA in duplicate. RESULTS: The median (25th-75th centile) age and birth week for all infants were 33 (29-43) days and 39 (38.1-40) weeks, respectively. Levels of Tsal in males [Group 1, 73.35 (59.94-117.82) pg/mL vs Group 2, 77.66 (56.49-110.08) pg/mL, p=0.956] and Esal in females [Group 1, 3.91 (2.76-5.31) pg/mL vs Group 2, 4.03 (1.63-12.1) pg/mL, p=0.683] were similar. However, in subjects with infantile colic (Group 1), Esal and body mass index (BMI) standard deviation scores of females were slightly correlated (Group 1, rs= 0.393, p=0.016 vs. Group 2, rs= 0.308, p=0.076) and there was a significant correlation between the sampling time and Tsal in males (Group 1, rs= 0.469, p=0.009 vs. Group 2, rs= -0.005, p=0.976). DISCUSSION AND CONCLUSION: Random salivary sex steroid levels were similar in infants with and without infantile colic. However, in subjects with infantile colic, Esal levels in females were positively correlated with BMI and Tsal levels were higher later in the day among males. Thus, sex steroid production may be altered during minipuberty in subjects with infantile colic.